دور البعثات العلمية المزابية إلى تونس في إعادة إنتاج القيم الوطنية - بعثة أبي اليقظان 1914-1926م أنموذجا - حمو, عبد الله عيسى (جامعة الوادي - University of Eloued, 2021)
لقد كانت سياسة فرنسا في طمس الهوية الدينية والوطنية من الجزائريين متماثلة بين الجنوب والشمال، وبين الشرق والغرب، والمجهودات التي قام بها رجال الإصلاح بالجزائر في سبيل التصدي لهذه السياسة واضحة وقد أتت أكلها، وتعد المؤسسات التربوية والبعثات العلمية آلية استعملها رجال الإصلاح في سبيل الإصلاح الديني والاجتماعي، ولعلّ من أبرز البعثات العلمية لسكان الجنوب الجزائري البعثة العلمية المزابية إلى تونس، والتي ترأسها أبو اليقظان من سنة 1914م إلى 1926م. في هذا المقال سنعرض نشأة وتطوّر البعثة العلمية المزابية إلى تونس، إلى جانب النظام التربوي والمقررات التي اِلتزم بها أعضاء البعثة العلمية المزابية، كما تناول المؤسسون والعلماء والزعماء، ودورهم التربوي وتشجيعهم الطلبة على الحفاظ على دينهم وشخصيتهم الوطنية، وتناولنا أيضا مشاركة أعضاء البعثة العلمية في الحزب الدستوري الحر التونسي، وأثره على إعادة إنتاج القيم الوطنية. Abstract : France's policy of obliterating the religious and national identity of the Algerians has been identical between the south and the north, and between the East and the West. The efforts made by the reformists in Algeria in order to confront this policy are clear and have paid off. Educational institutions and scientific missions were used by reformers for the sake of religious and social reforms. Among the most prominent scientific missions of the residents of southern Algeria is the Mozabite scientific mission to Tunisia, which was headed by Abu Al- Yaqdhan from 1914 to 1926. This article deals with the emergence and development of the Mozabite scientific mission to Tunisia, along with the educational system and the decisions that the members of this mission committed to. It displays its founders, scholars and leaders’ educational role and how they encouraged the students to preserve their religion and national personality. It also explores the participation of the members of the scientific mission in the Tunisian Free Destourian Party and its effect on reproducing the national values.
The Role of the Mozabite Scientific Missions to Tunisia in Preserving National Identity. The mission of Abu Al-Yaqdhan 1914-1926 as a Model
مقال
Keywords: البعثة العلمية؛ النظام التربوي ؛ وادي مزاب؛ أبو اليقظان؛ القيم الوطنية: the scientific mission; the educational system; the M'zab Valley; Abu Al- Yaqdhan ; the national values